PELAKSANAAN DIVERSI TERHADAP ANAK PELAKU TINDAK PIDANA DI KEJAKSAAN NEGERI PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The problem of implementing the diversion is not as expected, this can also be seen with the performance of the public prosecuting agency which is still breaking through legal channels where good law enforcement processes, responsible officials, adequate facilities and infrastructure, factors of society, as well as factors from culture, in the diversion process often conflicts occur between children in conflict with the law and victims. This study aims to determine the procedures for implementing diversion against children in conflict with the law by the Public Prosecutor, and inhibiting factors in the implementation of diversion and its solutions. The formulation of the problem in this research is the implementation of the diversion of children of perpetrators of crime in the Pekanbaru District Attorney's Office and the constraints in implementing the diversion of children of perpetrators of crime in the Pekanbaru District Attorney. The research method used is the type of research in this writing is juridical sociological. The type of research used is descriptive legal research. From the results of the research, the procedure for implementing the diversion by the Public Prosecutor is guided by two Laws Number 11 Year 2012 concerning the Child Criminal Justice System and Attorney General Regulation No. PER006/A/J.A/05/2015 concerning Guidelines for the Implementation of Diversity at the Prosecution Level. In the case of Andre Siswandi and Romi Septriansyah's children, Article 363 Paragraph 2 is charged where the article is threatened with a 9 (nine) year sentence, but law enforcement officials break the rules stipulated in Law Number 11 Year 2012 concerning the Juvenile Justice System with the Child Criminal Justice System with keep on doing diversion where the diversion should be carried out under the condition of a criminal under 7 (seven) years and not a repeat of a criminal offense. In addition, the implementation of diversion is often not conducive between the perpetrators and victims because each party does not want to heed what is desired by both parties. The conclusion of this research is that there is no agreement between the perpetrators and victims so that the agreement of diversion is very difficult to achieve. ineffective and inefficient in terms of facilities and infrastructure where the diversion space is still too small so that the process of reconciling between the perpetrators and victims becomes uncomfortable. Obstacles are posed difficult to reconcile the parties where the victim uses the situation to blackmail the victim, lack of understanding of diversion, narrow space of diversion, as well as law enforcers who participate in breaking through the law itself Solution to the obstacles is the awareness of the parties, the existence of legal counseling, improved diversion space. KeyWords: Diversity Implementation, Law EnforcemenT, Children